2018
DOI: 10.1016/j.ajoc.2018.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic subhyaloid macular hemorrhage with complete resolution following Neodymium-Doped Yttrium Aluminium Garnet Laser

Abstract: PurposeTo report a case of traumatic subhyaloid macular hemorrhage with severe sudden vision loss treated successfully with Neodymium-Doped Yttrium Aluminium Garnet Laser (Nd:YAG laser).ObservationsA 16-year-old boy presented to the eye clinic with acute vision loss secondary to blunt trauma by a stone to his left eye 3 days prior to consultation that caused subhyaloid macular hemorrhage. Nd:YAG laser was performed to open the hyaloid membrane and allow the blood to diffuse into the vitreous cavity and be abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…However, substandard VA in 50% of our cases resulted from an additional macular pathology due to diabetic retinopathy or CRVO. This is in keeping with several reports of favourable visual and anatomic results of the procedure in other populations [1], [2], [3], [4], [5], [6], [7], [8], [9], [10]. Khan showed a total of 11 out of 12 patients who underwent Nd-YAG had visual acuity improvement 16 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, substandard VA in 50% of our cases resulted from an additional macular pathology due to diabetic retinopathy or CRVO. This is in keeping with several reports of favourable visual and anatomic results of the procedure in other populations [1], [2], [3], [4], [5], [6], [7], [8], [9], [10]. Khan showed a total of 11 out of 12 patients who underwent Nd-YAG had visual acuity improvement 16 .…”
Section: Discussionsupporting
confidence: 90%
“…It aims to drain the trapped blood into the vitreous cavity by creating a puncture in the posterior hyaloid membrane and/ or ILM by using the photo-disruptive effect of YAG laser. Some previous studies reported favourable outcomes of NYPH in cases of PMSHH [1], [2], [3], [4], [5], [6], [7], [8], [9], [10]. We noticed that many retina specialists do vitrectomy surgery as a primary intervention for the condition.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…YAG laser hyaloidotomy for the treatment of sub-ILM hemorrhage was described in the literature, [8][9][10] and in certain cases, it has shown its effectiveness.…”
Section: Resultsmentioning
confidence: 99%